Implementasi Kebebasan Beragama di Baduy Tangtu Ditinjau dari Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan Hukum Islam - Hana Muthia; Siti Ngainnur Rohmah; Taufiqurachman Taufiqurachman (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Human Rights are meant for everyone one of which is ruling about religious freedom. Indonesia as a law state also has ruled the right of religious freedom for each of its citizens in The Constitution of the Republic of Indonesia Year 1945. Besides, Human Rights are also regulated in Islamic Law which its provision is ruled in the Medina Charter, Aelia Charter in Jerusalem, Al-Qur’an Verses, and Interpretation. This paper gives an understanding of the implementation of religious freedom in Baduy Tangtu reviewed from The Constitution of the Republic of Indonesia Year 1945 and Islamic law. This research employed qualitative descriptive research, with normative juridical and empirical approaches. The data sources used data through observation, interview, focused discussion, and questionnaire distribution in the field, books, journals, documents, law regulations, and so on. The research results showed that the religious freedom implementation in Baduy Tangtu is in line with the concept of religious freedom according to the constitutions of the Republic of Indonesia Year 1945 where everyone is free to embrace their own religion and worship according to that religion and belief. Besides, the results of this research also showed that the implementation of religious freedom in Baduy Tangtu has been in accordance with religious freedom according to Islamic law where everyone is not forced to embrace a certain religion and is allowed to do worship based on their own belief without any mix between one religion with other religion, and not hostiling someone because of their religion unless they disturb, bother, or hurt.Keywords: Implementation; Religious Freedom; Baduy Tangtu; The Constitution of Year 1945; Islamic Law AbstrakHak Asasi Manusia diperuntukkan bagi setiap orang dimana salah satunya mengatur tentang Kebebasan Beragama. Indonesia sebagai negara hukum juga telah mengatur hak kebabasan beragama bagi setiap warganya di dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Selain itu, Hak Asasi Manusia juga diatur di dalam Hukum Islam yang ketentuannya diatur di dalam Piagam Madinah, Piagam Aelia di Yerussalem, Ayat-Ayat Al-Qur’an, dan tafsir. Tulisan ini memberikan pemahaman mengenai implementasi kebebasan beragama di Baduy Tangtu ditinjau dari Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan hukum Islam. Penelitian ini menggunakan metode penelitian kualitatif, dengan pendekatan yuridis normatif dan empiris. Sumber data yang digunakan adalah data dari observasi, wawancara, diskusi terfokus, dan penyebaran kuesioner di lapangan, buku, jurnal, dokumen, peraturan perundangan, dan sebagainya. Hasil penelitian menunjukkan bahwa implementasi kebebasan beragama di Baduy Tangtu sesuai dengan konsep kebebasan beragama menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dimana setiap orang bebas memeluk agamanya masing-masing dan beribadat menurut agama dan kepercayaannya itu. Selain itu, hasil penelitian juga menunjukkan bahwa implementasi kebebasan beragama di Baduy Tangtu sesuai dengan konsep kebebasan beragama menurut Hukum Islam dimana setiap orang tidak dipaksa memeluk suatu agama dan dipersilahkan beribadat menurut keyakinan masing-masing tanpa adanya campur aduk ritual beribadah antara agama yang satu dengan yang lain, serta tidak memusuhi seseorang karena agamanya kecuali orang tersebut mengganggu, mengusik, atau menyakiti.Kata Kunci: Implementasi; Kebebasan Beragama; Baduy Tangtu; Undang-Undang Dasar Tahun 1945; Hukum Islam